Virtual Realities. - Jackson, D. D. (Downbeat, 2007)
The article comments on the use of computer-based instruments in live musical performances in the U.S. Controversy has clouded the use of computer programs that enable the live playback of virtual orchestras controlled by an operator through computers. The issue requires musicians to strike a balance between the inevitable emergence of musical technology and the preservation of live musical performances.